Immunological efficacy of herbal medicines in prostate cancer patients treated by personalized peptide vaccine. Issue 12 (3rd October 2017) - Koga, Noriko; Moriya, Fukuko; Waki, Kayoko; Yamada, Akira; Itoh, Kyogo; Noguchi, Masanori
Abstract : This randomized phase II study investigated the immunological efficacy of herbal medicines (HM) using Hochu‐ekki‐to and Keishi‐bukuryo‐gan in combination with personalized peptide vaccination (PPV) for castration‐resistant prostate cancer (CRPC). Seventy patients with CRPC were assigned to two arms; PPV plus HM or PPV alone. Two to four peptides were chosen from 31 peptides derived from cancer antigens for a s.c. injection of PPV given eight times according to the patient's human leukocyte antigen type and levels of antigen‐specific IgG titer before PPV treatment. Peptide‐specific CTL, IgG, regulatory T cells (Treg), monocytic myeloid‐derived suppressor cells (Mo‐MDSC), and interleukin‐6 (IL‐6) responses were measured before and at the eighth vaccination. Clinical outcomes were also analyzed. Combination therapy of PPV with HM was well tolerated without severe adverse events. There was no significant change in antigen‐specific IgG, CTL, Treg or clinical outcomes. Combination therapy of PPV with HM stabilized the frequency of Mo‐MDSC (1.91%–1.92%, P = 0.96) and serum levels of IL‐6 (19.2 pg/mL to 16.1 pg/mL, P = 0.63) during the treatment. In contrast, the frequency of Mo‐MDSC and levels of IL‐6 in the PPV‐alone group were significantly increased (0.91%–1.49% for Mo‐MDSC and 9.2 pg/mL to 19.4 pg/mL for IL‐6, respectively). These results suggest that the combined use of HM has the potential to prevent the immunosuppression induced by Mo‐MDSC or IL‐6 during immunotherapy. More research is needed to validate the findings of the present study. Abstract : In this randomized, phase 2 clinical trial, the combination therapy of personalized peptide vaccination with herbal medicines using Hochu‐ekki‐to and Keishi‐bukuryo‐gan, stabilized the frequency of immunosuppressive monocytic myeloid‐derived suppressor cells and serum levels of IL‐6 during the treatment.